2021
DOI: 10.1007/s00343-021-0029-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and diversity of magnetotactic bacteria from sediments of Caroline Seamount in the Western Pacific Ocean

Abstract: Magnetotactic bacteria (MTB) are a group of microorganisms capable of orientating and swimming along magnetic fields because they contain intracellular biomineralized magnetosomes composed of magnetite (Fe 3 O 4 ) or/and greigite (Fe 3 S 4 ). They are ubiquitous in freshwater, brackish, and marine habitats, and are cosmopolitan in distribution. However, knowledge of their occurrence and distribution in seamount ecosystems is limited. In this study we investigated the diversity and distribution of MTB in the Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Chen et al (2021b) examine the morphological and phylogenetic diversity of MTB in a mangrove environment and demonstrate the existence of a highly diverse group of MTB in this productive ecosystem at the transition between terrestrial and marine environments. Cui et al (2021) extend the studies of MTB diversity and distribution to the Caroline Seamount located in the south of the Mariana Trench. Interestingly, the authors have revealed the occurrence of abundant living MTB cells in sediments at water depths >1 500 m. This fi nding, together with the previous studies (e.g., Petermann and Bleil, 1993;Liu et al, 2017), reinforces the widespread distribution of MTB in bathypelagic environments.…”
mentioning
confidence: 76%
“…Chen et al (2021b) examine the morphological and phylogenetic diversity of MTB in a mangrove environment and demonstrate the existence of a highly diverse group of MTB in this productive ecosystem at the transition between terrestrial and marine environments. Cui et al (2021) extend the studies of MTB diversity and distribution to the Caroline Seamount located in the south of the Mariana Trench. Interestingly, the authors have revealed the occurrence of abundant living MTB cells in sediments at water depths >1 500 m. This fi nding, together with the previous studies (e.g., Petermann and Bleil, 1993;Liu et al, 2017), reinforces the widespread distribution of MTB in bathypelagic environments.…”
mentioning
confidence: 76%
“…In contrast, MTB in deep-sea environments is largely unknown, partly because the low cell density of MTB hinders the magnetic recovery of magnetotactic cells sufficiently for FISH and single-cell genomics. In deep-sea sediments, magnetosomes have been observed with microbial cells (Liu et al, 2017 ; McGlynn et al, 2018 ; Cui et al, 2021 ), whereas magnetosomes have been observed without microbial cells (Dong et al, 2016 ; Yamazaki et al, 2019 ). Although the previous deep-sea studies attempted to clarify the taxonomy of MTB involved in the formation of magnetosomes by 16S rRNA gene sequences, metagenomic analysis was performed to characterize MTB, the presence of which has been demonstrated by electron microscopy in deep-sea hydrothermal sediments (Chen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…MVB is a hallmark of eukaryotic cells and their formation depends on ESCRT machinery including ESCRT-III proteins that function in membrane remodeling, repairing and membrane abscission in cytokinesis in eukaryotic cells 2 . Recently, phylogenetic and structural studies have shown that bacterial Vipp1/Imm30 and PspA proteins are members of the ESCRT-III membrane-remodeling superfamily, which plays pivotal role in maintaining membrane integrity and thylakoid biogenesis, and is capable of remodeling lipid bilayers in vitro [3][4][5][6] . This finding paves the way toward a better understanding of the mechanism of compartmentalization in the primitive cells of bacteria.…”
Section: Introductionmentioning
confidence: 99%